Efektivitas Model Blended Learning Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Zoologi di Era Covid-19: (The Effectiveness of the Blended Learning Model on Student Learning Outcomes in Zoology Subjects in the Covid-19 Era) - Tomi Apra Santosa; Abdul Razak; Azwir Anhar; Ramadan Sumarmin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The purpose of this study was to determine the differences between the blended learning and offline method models on student learning outcomes in the COVID-19 pandemic. The research used was experimental. The research subjects came from 5-semester biology tadris students of the 2019/2020 academic year IAIN Kerinci. Research instruments in the form of tests and questionnaires via a google form. The data analysis technique was in the form of the t-test with Minitab 19 software. To carry out the hypothesis test, the normality test and the homogeneity test had to be done first. The results showed that the blended learning model was effective in increasing student learning outcomes in the zoology course by an average of 68.16 to 83.42. and provide a significant effect of the blended learning model on student learning outcomes in zoology material. This can be seen from the p-value of 0.000 <0.05. The blended learning model is very good to be applied in schools even in universities where this learning model is able to improve student learning outcomes in the era of the COVID-19 pandemic. Abstrak. Tujuan penelitian ini mengetahui perbedaan model blended learning dan luring method terhadap hasil belajar biologi siswa pada pandemi COVID-19. Penelitian yang digunakan eksperimen. Subjek penelitian berasal dari mahasiswa tadris biologi semester 5 tahun ajaran 2019/2020 IAIN Kerinci. Instrumen penelitian berupa tes dan angket melalui google form. Teknis analisis data berupa uji t dengan sofware Minitab 19. Untuk melaksanakan uji hipotesis, maka harus dilakukan dahulu uji normalitas dan uji homegenitas data. Hasil penelitian menunjukan bahwa model blended learning efektif meningkatan hasil belajar mahasiswa pada mata kuliah zoologi dengan rata-rata 68.16 menjadi 83.42. dan memberikan pengaruh signifikan model blenden learning terhadap hasil belajar mahasiswa pada materi zoologi. Hal dapat dilihat dari nilai p-value 0.000 < 0.05. Model blended learning sangat baik untuk diterapkan di sekolah bahkan di perguruan tinggi dimana model pembelajaran ini mampu meningkatkan hasil belajar mahasiswa di era pendemi covid 19.